Analysis of User Perceptions of Shopee’s Delivery Service Quality in the Jabodetabek Area - Marbun, Syfa Putri Soleha; Saharani, Putri; Santoso, Muhammad Dafa; Lestari, Hasna Atika Candra; Zakiah, Rizka (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2024)
The advancement of digital technology has significantly transformed consumer shopping behavior, with e-commerce platforms such as Shopee becoming the primary choice for Indonesian consumers, particularly in the Greater Jakarta area (Jabodetabek). This study aims to analyze user perceptions of Shopee’s delivery services. Employing a qualitative approach, data were collected through an online questionnaire distributed to 212 respondents residing in the Jakarta, Bogor, Depok, Tangerang, and Bekasi region. The findings reveal that most respondents hold a positive perception of Shopee’s delivery services, especially in terms of delivery timeliness, package tracking, and the variety of available courier options. Free shipping promotions also contribute significantly to strengthening users’ positive perception. However, some users reported dissatisfaction with the lack of flexibility in scheduling deliveries or adjusting delivery routes. These findings reinforce previous studies indicating that delivery quality particularly speed and reliability plays a vital role in shaping user perceptions of e-commerce services. Shopee is advised to enhance its delivery flexibility to better meet user needs and expectations. Improving these aspects can strengthen user satisfaction and maintain Shopee’s competitive advantage in Indonesia’s growing e-commerce industry